Employing the principal components in time series models and selecting the best models with Application - Rizgar Maghded Ahmed; Nida Salim Mala Younis (Zanco Journal of Humanity Sciences)
In this study, principal components analysis, which is one of the methods of multivariate analysis for prediction of time series models (Box-Jenkins Model) was used by applying to electric power data (Erbil Gas Power Plant) (EGPS) which contains multivariate data (5 stations) and the data was monthly for the period from (1/1/2017) to (14/9/2021).